1970
DOI: 10.3126/nepjoph.v1i2.3682
|View full text |Cite
|
Sign up to set email alerts
|

Phacoemulsification versus small incision cataract surgery (SICS): which one is a better surgical option for immature cataract in developing countries?

Abstract: Background: Several studies have shown comparable visual outcomes of SICS and phacoemulsification (Gogate et al 2007, Ruit et al 2007.Objective: To compare the safety and efficacy of different types of surgical procedures (phacoemulsification versus SICS) for cataract surgery in immature cataract. Material and methods:A prospective randomized controlled trial was carried out involving 93 and 89 patients with immature senile cataract selected for phacoemulsification and SICS respectively. Statistics:Mean values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

1970
1970
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…Gogate et al 15 revealed that mSICS was almost half the cost of phacoemulsification with easier learning curves. Moreover, Singh et al 8 showed that sterilization procedures for mSICS is more available and inexpensive than phacoemulsification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gogate et al 15 revealed that mSICS was almost half the cost of phacoemulsification with easier learning curves. Moreover, Singh et al 8 showed that sterilization procedures for mSICS is more available and inexpensive than phacoemulsification.…”
Section: Discussionmentioning
confidence: 99%
“…7 However, several comparable previous studies in Nepal have shown similar visual outcomes from both mSICS and phacoemulsification but there are no studies yet in Indonesia that report the significance of each visual outcome after the surgery. 8 Similar studies in Egypt also stated that there were insignificant results of uncorrected visual acuity (UVCA) and best corrected visual acuity (BCVA) of patients who underwent phacoemulsification versus mSICS. 7,9 In the Department of Ophthalmology, Faculty of Medicine, Public Health and Nursing, Universitas Gadjah Mada, Yogyakarta, Indonesia, outreach cataract programs have been conducted frequently with approximately 15-20 programs annually.…”
Section: Introductionmentioning
confidence: 93%
“…A total of 14 potential controlled clinical trials relevant to a comparison of the PE and MSICS were identified through the search. [15][16][17][18][19][20][21][22][23][24][25][26][27][28] Eight studies were excluded; seven lacking primary outcome data, [16][17][18][19][20][21][22] two reporting on the same subjects 15,23 integrated into one study. 23 Thus, a total of six RCTs were included in the final meta-analysis.…”
Section: Identification and Selection Studiesmentioning
confidence: 99%
“…The attempt of Singh et al (2009) to justify the rationale of the widely used small incision cataract surgery (SICS) in developing countries is impressive. The technique used in the SICS by the principle author in immature cataract seems to be ideal that the external and internal wound size remains the same.…”
mentioning
confidence: 99%